Nutritional implications of mate harvesting: a case study in southwestern Paraná State, Brazil - Brun, Eleandro José; Brun, Flávia Gizele König; Mezzalira, Carlos César; Frigotto, Taciana (Revista Ecologia e Nutrição Florestal - ENFLO, 2014)
We assessed the biomass and nutrients accumulated in trees and the nutritional implications of biomass harvesting from a mate plantation in the southwestern region of Paraná State, Brazil. The plantation comprised 173 trees, at eight years of age, planted in 2 m x 2 m spacing, with seminal seedlings produced in plastic bags and the planting was carried out in groves with no nutrients added. We randomly chose five trees that were cut low to the ground and their biomass was separated into fractions: trunk (wood + bark), thick branches (diameter > 1 cm), fine branches (diameter ≤ 1 cm) and leaves, and the last two fractions were evaluated regarding their use in the mate industry. The nutrient contents in the fractions were determined in samples from the five trees. The total moist biomass reached 55.05 Mg ha-1, with leaves (20.0%), fine branches (11.4%), thick branches (14.6%) and trunk (54.1%). The total dry biomass reached 21.81 Mg ha-1, with leaves (20.5%), fine branches (12.0%), thick branches (14.9%) and trunk (52.6%). The highest nutrient contents occurred in the leaves (except for P) and fine branches, and N had the greatest content for both fractions. The site productivity was considered average, with 12.07 Mg ha-1 or 804.7 arrobas ha-1 for 80% of economically usable fractions (leaves and fine branches), a situation for which the harvesting is recommended due to the least nutritional impact.